Introduction to theories of social change - Strasser, Hermann; Randall, Susan C. (London, Routledge and kegan paul, 1981)
Addressed to students of the social sciences interested in conceptualizing and explaining change phenomena on various levels of society, this introductory text deals with central questions in an increasingly important field, and systematically examines alternative and complementary theoretical approaches. The first with the assumptions underlying any analysis of change, with the dimensions of social change (such as scope, direction and speed) and with the most important theories explaining such change. The second part deals with the structural functionalist and historical materialist approaches in detail, and assesses their explanatory potential. Finally, the third part compares the various approaches already described, by means of illustrative case studies of change at the different levels of society (interaction, group, organization and social system).
Keywords: Sociology